Pengaruh Pemberian Pupuk Organik Berbahan Daun Kering, Kotoran Sapi, EM4, dan Molase terhadap Pertumbuhan Tanaman Pakcoy (Brassica rapa L) - Dian Putri Lestari; Marisa Sitanggang; Nur Afliza; Putri Nurlela Nasution; Rika Lidia Sibarani; Yokhe Maria Anastasya Tampubolon; Bunga Ria Sitanggang (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aimed to evaluate the effect of solid organic fertilizer made from dry leaves, cow manure, EM4, and molasses on the growth of pakcoy (Brassica rapa L.). The experiment was conducted using a Completely Randomized Design (CRD) with four treatments: control (no fertilizer), and fertilizer applications at concentrations of 15%, 30%, and 35%, each replicated three times. Observed parameters included plant height, number of leaves, and fresh weight. Data were analyzed using ANOVA followed by the Least Significant Difference (LSD) test at a 5% significance level. The results showed that the application of solid organic fertilizer significantly affected the growth of pakcoy. The 30% concentration yielded the best results, with an average plant height of 18.3 cm, 10 leaves per plant, and a fresh weight of 22.5 grams. Statistical analysis confirmed significant differences among treatments (p < 0.05). These findings indicate that applying 30% solid organic fertilizer effectively enhances pakcoy growth and supports sustainable organic farming practices.